2014
DOI: 10.1002/mus.24196
|View full text |Cite
|
Sign up to set email alerts
|

Changes in motor unit properties in SOD1 (G93A) rats

Abstract: Changes in MU properties of SOD1 rats have progressive and multidirectional character and speed depending on the MU type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…A previous study of the medial gastrocnemius of SOD1G93A rats, found there to be a loss of FF motor units and increase in proportion of S motors units in late stage disease, which match our twitch timing observations slowing down over time 18 . Furthermore, the study found motor unit rise times of fast motor unit types increased in early symptomatic animals.…”
Section: Measurements Of Rise Times Likely Reflect the Altered Distrisupporting
confidence: 91%
“…A previous study of the medial gastrocnemius of SOD1G93A rats, found there to be a loss of FF motor units and increase in proportion of S motors units in late stage disease, which match our twitch timing observations slowing down over time 18 . Furthermore, the study found motor unit rise times of fast motor unit types increased in early symptomatic animals.…”
Section: Measurements Of Rise Times Likely Reflect the Altered Distrisupporting
confidence: 91%
“…In contrast, other slow type MNs undergo a hyperexcitable shift in rheobase similar to fast type MNs [ 42 ]. In SOD1 mutant rats, in the terminal phase of the disease, slow MNs reinnervate fast muscle fibers and gain some properties of fast motor units [ 43 ]. Recently, it has been shown in the SOD1-G85R mouse model that MMP9-immunopositive MNs are present in the spinal ventral horn at 4 months of age while electrophysiological investigation reveals a massive loss of fast type MNs at that stage [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results may not necessarily reflect the behaviour of motor neurones with higher recruitment thresholds. For instance, selective degeneration (Hadzipasic et al., 2014) and accentuated hypo‐excitability (which seems to precede denervation) (Kryściak et al., 2014; Martínez‐Silva et al., 2018) are more prominent in larger motor neurones in rat models of ALS. ALS is a highly heterogenous neurological disease, and different pathology characteristics might play distinct roles in controlling PICs and its effects on motoneuron intrinsic excitability, such as disease stage and rate of progression, site of onset (e.g.…”
Section: Discussionmentioning
confidence: 99%